1998
DOI: 10.1021/jf9804443
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Activities of Chymosin and Porcine Pepsin on Buffalo, Cow, and Goat Whole and β-Casein Fractions

Abstract: The proteolytic specificity and activity of a recombinant chymosin (Maxiren) and porcine pepsin on buffalo, cow, and goat whole casein (CN) and β-CN were studied by analyzing the degradation products. The results suggest that the hydrolysis of whole casein of buffalo and goat by chymosin was similar to that of cow casein resulting in αs1-I and β-I, -II, and -III as degradation fragments of αs1- and β-CN. The exception was goat β-I which was resistant to further hydrolysis by chymosin but not to porcine pepsin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 19 publications
4
24
0
Order By: Relevance
“…2009). Cryphonectria parasitica protease is less characterised, but it is generally acknowledged that its total proteolytic activity is higher (Tam and Whitaker 1972; Vanderporten and Weckx 1972) and that, in contrast to protease from Rhizomucor , mainly β‐casein is hydrolysed (Ustunol and Zeckzer 1996; Awad et al. 1998, 1999; Trujillo et al.…”
Section: Chemistry and Production Technologymentioning
confidence: 99%
“…2009). Cryphonectria parasitica protease is less characterised, but it is generally acknowledged that its total proteolytic activity is higher (Tam and Whitaker 1972; Vanderporten and Weckx 1972) and that, in contrast to protease from Rhizomucor , mainly β‐casein is hydrolysed (Ustunol and Zeckzer 1996; Awad et al. 1998, 1999; Trujillo et al.…”
Section: Chemistry and Production Technologymentioning
confidence: 99%
“…This may have an effect on the hydrolysis of caseins. Increasing of NaCl concentration (from X5% to 10%) reduced the proteolysis of b-casein in casein solutions (Awad, Luthi-Peng, & Puhan, 1998); the hydrolysis of a s1 -casein was not inhibited by the high NaCl concentration (e.g., 10%) (Awad, Luthi-Peng, & Puhan, 1999a). Starter proteinases have contributed to a small extent to the initial degradation of b-casein (Awad, Luthi-Peng, & Puhan, 1999b).…”
Section: Urea-pagementioning
confidence: 99%
“…Therefore, the electrophoretic differences between the samples regarding a s1 -CN degradation products could be attributed to the differences in the peptidases and ⁄ or aminopeptidases activities of the strains used. It was reported that the hydrolysis of a s -CN was not completely inhibited by NaCl concentration (Awad et al 1998). In all samples, the bands representing c 1 -CN (b-CN f29-209), c 2 -CN (b-CN f106-209) and c 3 -CN (b-CN f108-209) became evident, being slightly fader in the cheese MBLL23.…”
Section: Electrophoresismentioning
confidence: 73%
“…Therefore, the electrophoretic differences between the samples regarding α s1 ‐CN degradation products could be attributed to the differences in the peptidases and/or aminopeptidases activities of the strains used. It was reported that the hydrolysis of α s ‐CN was not completely inhibited by NaCl concentration (Awad et al. 1998).…”
Section: Resultsmentioning
confidence: 99%